‘Limiting the Customer’s Freedom to Decide by Using Particularly Aggressive Sales Methods’ in Terms of Unfair Competition Law (TCC 55.1.a.8) - Burçak Yıldız (İstanbul Hukuk Mecmuası)
According to Turkish Commercial Code (TCC) 55.1.a.8, affecting customers’ freedom to decide using aggressive sales methods causes unfair competition. The physical or psychological pressure exerted on a customer is considered aggressive only if harassment, coercion, or undue influence is considered. In the Wind Tre SpA Decision of the Court of Justice of the European Union (CJEU), selling SIM cards on which internet-browsing and voicemail services are preloaded and pre-activated, without informing customers of that pre-loading and pre-activation, is considered an aggressive commercial practise. According to the Orange Polska Decision of the CJEU, the fact that a customer takes the final transactional decision in the presence of a courier without being freely able to take cognisance of the content of that contract does not constitute an aggressive commercial practise in all circumstances. The fact that the elements of the provision are not clearly indicated in TCC 55.1.a.8 causes the application of this provision to actions that are not intended by the Code. The Turkish Court of Cassation found that sharing a link on the internet to show how football matches over which the plaintiffs have a broadcast monopoly can be watched free of charge violates this provision. We criticise this judgement since there is no harassment, coercion, or undue influence in this incident. Aggressive advertisements are excluded from the scope of the provision because they are not qualified as “sales method”. Persistent and unwanted solicitations are also not covered by TCC 55.1.a.8 unless they are personalised on behalf of the customer. Aggressive commercial practises are also regulated by consumer acquit (Commercial Advertising and Unfair Commercial Practises Regulation 31). However, TCC 55.1.a.8 maintains its importance for consumers because it brings the criminal liability of the defendant and gives consumer organisations the right to sue.